Tactical nuclear weapons emergent threats in an evolving security environment - Alexander, Brian; Millar, Alistair (Brassey's, 2003)
Detailing all the pertinent issues concerning tactical nuclear weapons, this volume contains the reliable estimate of the size of the Russian tactical nuclear arsenal.